An alternative explanation of the prize puzzle - Paolo Giordani (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
This paper proposes a simple explanation for the frequent appearance of a price puzzle in VARs designed for monetary policy analysis. It suggests that the best method of solving the puzzle implies a close connection between theory and empirics rather than the introduction of a commodity price. It proves that the omission of a measure of output gap (or potential output) spuriously produces a price puzzle (and several other incorrect conclusions) in a wide class of commonly used models. This can happen even if the model admits a triangular identification and if the forecasts produced by the misspecified VAR are optimal. When the model is tested on US data, all predictions are supported.
Keywords: E30; E52; 330; Price puzzle; monetary policy; misspecification; output gap; potential output; technology shocks; VAR; Geldpolitik; Inflation; Schock; Gesamtwirtschaftliche Produktion; VAR-Modell; Theorie